Insights Into miRNA-mRNA Regulatory Mechanisms of Cold Adaptation in Gymnocypris eckloni: Ubiquitin-Mediated Proteolysis Is Pivotal for Adaptive Energy Metabolism - Nie, Miaomiao; Ni, Weilin; Wang, Lihan; Gao, Qiang; Liu, Dan; Tian, Fei; Wang, Zhenji; Zhang, Cunfang; Qi, Delin (Frontiers in Genetics, 2022)
In this study, we aimed to understand cold-stress adaptations mechanism in fish. Consequently, the transcriptional response to cold conditions in Gymnocypris eckloni was evaluated using RNA-seq and microRNA (miRNA)-seq analyses. Low temperature (LT) group G. eckloni were cultivated outdoors in waters cooled to 2–4°C for 3 weeks, while individuals in the control temperature (CT) group were exposed to 14–16°C. Significantly different responses were observed in both mRNA and miRNA expression profiles, with more mRNAs (1,833 and 1,869 mRNAs were up- and downregulated, respectively) and fewer miRNAs (15 and 6 were up- and downregulated, respectively) observed in the LT group individuals relative to CT individuals. A miRNA-mRNA network involved in the regulation of G. eckloni responses to cold stress was constructed; this network included ubiquitin-mediated proteolysis, protein processing, and oxidative phosphorylation. These results provided new insights into mechanisms of cold tolerance by fish, including decreased metabolic activity in addition to proteolysis.